INVOLUTIVE DENTAL ASPECTS IN THE GERIATRIC PATIENT - IMPLICATIONS IN SPECIFIC THERAPY - Iordache Cristina Marina; Lodbă Alexandru; Țarevici Eugenia Larisa; Ana Maria Fătu; Bogdan Vâscu; Antohe Magda Ecaterina (Romanian Dental Association for Education, 2022)
The existential problems encountered by elderly patients are influenced by a series of parameters (physical, medical, psychological, or social) that make it difficult for them to carry out normal activities and can amplify the pathology of this fragile population category. Dental caries is quite common in the elderly patient, although we are tempted to believe that elderly teeth are less susceptible to caries due to involutional structural changes. As a chronic, slowly evolving infectious process with certain peculiarities, dental caries progresses in densified and hypermineralised tissues, both at coronal level but prevalent at root level. Clinically in the early stage the initial lesion appears on the proximal, buccal, or oral surface at the enamel/cement junction as one or more small, creamy, brownish, round, elliptical or fissural dots or spots (pigmentations) which merge, tend to expand, become circular, surround the root and encompass all surfaces closely forming serpiginous caries. Tending to progress circumferentially on the surface and not in depth, it causes weakening of the crown-root junction, with significant dental destruction, with splinter-like detachment of tissue, with increased risk of fracture. Dental medicine must consider the elderly as a complex being, an entity with a specific bio-psycho-social structure, with an individualised pathology of the dental system arising from physiological involution.